Finalization of transportation construction contract management at Project Management Unit No.7 under Ministry of Transport, Viet Nam - Tuan Anh Nguyen; Nam Ha Nguyen (International Journal of Scientific Research in Civil Engineering, 2021)
Managing the many contracts related to a construction project can be hard and time-consuming. Therefore, researching to learn about construction contracts and construction contract management to determine the current situation, causes and propose solutions to overcome is essential for businesses and agencies. State authority in construction activities. In addition, the management of contract performance after the result of contractor selection and contract signing is a subject of special concern of the Investor, the contractor and the whole society. This article explains construction contract in terms of generic contract provisions and recommend solutions for completing contract management at PMU 7 under the Ministry of Transport, Vietnam.